BENEFITS OF MANGROVE MANAGEMENT FOR PRAWN FISHING AND TIMBER PRODUCTION - Bagus Oktori Sutrisno; Slamet Budi Prayitno (Indonesian Fisheries Research Journal, 2013)
Integrated fisheries resource management is absolutely needed to achieve optimal result and sustainable utilization. This research aims to analyze the benefit of mangrove forest management for prawn fishing and mangrove timber production in Segara Anakan, southern coast of Central Java. The information concerning mangrove coverage changes was achieved from a satellite imagery (Landsat) from 2002 to 2009, while prawn resources stock assessment was analyzed through production surplus method and economic analysis of prawn fishing. The results show that the condition of mangrove ecosystem in Segara Anakan since 2002 to 2009 had been decreasing with average decrease rate of 10,28% each year which caused to prawn abundance. Utilization of mangrove wood inwhich aged above 20 years would give more benefit to prawn fishing and timber production. The additional economic value for prawn fishing was approximately 3,964 times of cropped woods. Prawn fisheries resource management in Cilacap coastal waters could be done by management of fishing effort and rehabilitation of mangrove forest in Cilacap region and surrounding areas as well especially in Segara Anakan Lagoon.